Position tracking control of an electromechanical hip-knee-ankle-foot orthosis / Zulkiffli Abd Kadir ... [et al.] - Abd Kadir, Zulkiffli; Alias, Muhammad Akhmal Hakim; Azman, Aina Nabila; Hudha, Khisbullah (UiTM Press, 2025)
The walking ability of the elderly is a major global health concern. Most of the elderly experience walking difficulties such as decreased walking speed and loss of balance as well as coordination. To address this issue, a mechanical orthosis called the hip-knee-ankle-foot orthosis (HKAFO) has been designed to assist elderly individuals and hospital patients in performing therapeutic treatments. However, the existing standard HKAFOs have several limitations including high energy consumption and overloading of the hip and lower limb joints during walking activities. Therefore, this study aims to enhance the standard HKAFO by developing an electromechanical HKAFO (EM-HKAFO). The study involves developing a two-degree-of-freedom mathematical model of a double pendulum using Lagrange formulation to represent the HKAFO structure and evaluate the kinematic motions of the lower limbs. The performance of the proposed walking aid is evaluated using an actual instrumented EM-HKAFO focusing on its effectiveness in achieving a desired walking angle of 25º. The result indicates that the difference between simulation and experimental data is within an acceptable error range of 14%. Overall, this study contributes to the advancement of mobility aids and enhances the quality of life for elderly individuals and patients in need.